Reform Experience with the Tanzanian Cotton Sector - Baffes, John (World Bank, Washington, DC, 2012)
Cotton, Tanzania's second largest crop after coffee, was introduced at the turn of the century by German settlers as a plantation crop but later efforts focused on smallholder production. Output rose considerably with the releases of new varieties, along with better organization of the sector following establishment of the Tanganyika Lint and Seed Marketing Board in 1956. By 1966, production reached 80,000 tons, or 0.75 percent of world production of 10.7 million tons.